Prevalence of nutritional anemia in children of high socioeconomic status in a tertiary care center - Kalaiselvam, Pradeep; Chelliah, Suresh; Pachamuthu, Meganathan (Indian Journal of Child Health, 2021)
Background: Anemia is a highly prevalent condition developed in children belonging to all socioeconomic status and is mainly caused due to iron deficiency in nutrition. Aim: To identify the Prevalence of nutritional anemia in children of high socioeconomic status. Methods: Children between 6 months and 14 years of age belonging to high socioeconomic status, admitted in pediatric ward of Kauvery Hospital, a tertiary center at Trichy were included in the study. Children with hemolytic anemia, chronic illnesses, and those who received blood transfusion were excluded from the study. The World Health Organization classification was used for grading the severity of anemia as mild, moderate, and severe based on hemoglobin levels for the age. Modified Kuppuswamy scale 2016 was used to assess the socioeconomic status of the children. Children belonging to upper and upper middle socioeconomic status were included in the study. Results: The overall prevalence of anemia among the study population was 44.5%. Out of 400 subjects, 178 participants were anemic. Of the 178 anemic children, 78.1% were in the age group of 6 months–5 years, 20.2% in 5–11 years, and 1.7% in 12–14 years. Among children between 6 and 23 months, 75 were anemic. Almost all patients showed microcytic hypochromic anemia. There were a significantly higher number of overweight and obese children among those anemic in all age groups. Conclusion: This study concludes that every other child is anemic even in families of high socioeconomic status, especially